2021
DOI: 10.1001/jamanetworkopen.2021.2544
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Protective Caregiving to Create Positive Racial-Ethnic Socialization and Mitigate Psychological Outcomes of Racial Discrimination

Abstract: Mitigating the complex longitudinal consequences racism can have on adolescents and their families is challenging. One strategy focuses on racial-ethnic socialization, the process by which society sends messages to individuals about the significance of their race, ethnicity, or cultural values. 1 In a secondary analysis comparing 2 unblended randomized clinical trials of rural Georgia-based familycentered prevention programs originally designed to prevent high risk sexual behavior and substance use by enhancin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…However, meta-analyses have found that common risk factors, including sociodemographic characteristics, psychological factors, physical health, and social relationships, yield limited predictive power for fatal and nonfatal suicidal behavior 6,7 . Besides, suicide risk factors are typically identified through association studies and do not fully account for potential confounding 6 .With the increasing availability and acceptance of integrative health practices, recent literature has suggested strength-based positive psychological interventions as a promising new approach to preventing suicide [8][9][10][11] . These well-being-focused suicide prevention programs can enhance social determinants of health (SDoH) via early intervention among high-risk populations, thus reducing individual and structural burdens of suicidal behaviors.Flourishing reflects a comprehensive assessment of well-being, with multiple complementary frameworks currently being the subject of research [12][13][14][15] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, meta-analyses have found that common risk factors, including sociodemographic characteristics, psychological factors, physical health, and social relationships, yield limited predictive power for fatal and nonfatal suicidal behavior 6,7 . Besides, suicide risk factors are typically identified through association studies and do not fully account for potential confounding 6 .With the increasing availability and acceptance of integrative health practices, recent literature has suggested strength-based positive psychological interventions as a promising new approach to preventing suicide [8][9][10][11] . These well-being-focused suicide prevention programs can enhance social determinants of health (SDoH) via early intervention among high-risk populations, thus reducing individual and structural burdens of suicidal behaviors.Flourishing reflects a comprehensive assessment of well-being, with multiple complementary frameworks currently being the subject of research [12][13][14][15] .…”
mentioning
confidence: 99%
“…With the increasing availability and acceptance of integrative health practices, recent literature has suggested strength-based positive psychological interventions as a promising new approach to preventing suicide [8][9][10][11] . These well-being-focused suicide prevention programs can enhance social determinants of health (SDoH) via early intervention among high-risk populations, thus reducing individual and structural burdens of suicidal behaviors.…”
mentioning
confidence: 99%